(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
Bowlby’s attachment theory is one of the psychological object relations theories. The pedagogic consequences of this concept are verifiable. In this study based on the attachment theory we define the relevant components of the social emotional relations during the infancy. The attachment network approach manner provides the starting point of the statements. The persons who are emotionally close to us, with whom we develop strong connections in our life belong in the hierarchical attachment system. These relationships determine the development of the personality. The development of relations with the emotionally closest people and the change of their content can be analysed inside the family and the early educational institutions.